Information Systems Management - Truong, Cong Doan (Khoa Quốc tế, ĐHQGHN, 2020)
This course promotes an understanding of the role of IT in the strategic planning of an enterprise; promotes an understanding of the interaction of IT with the structure and culture of an enterprise; promotes an understanding of the need for, and the techniques of, introducing change and innovation into an organization, especially the introduction or expansion of IT. This course will also give the students theoretical knowledge about MIS project management as well as the chance to practice on software solutions such as Microsoft Project and Tableau that are in great demand in the job market in the field.